EFL Students’ Perception on E-Learning in Post-Pandemic: Assessment, Learning Outcome, Evaluation & Problem Faced - Mu'in, Fatchul; Mariani, Nanik; Nasrullah, Nasrullah; Amelia, Rizky (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2023)
Online learning has been experienced by students worldwide with benefits and challenges. Even though previous research has been done on the unreadiness of teachers and students, their lack of technological skills, and their lack of autonomy in carrying online learning, more is needed to know about the washback effect of online learning from the perspective of learners. Thus, this research investigates students' assessment, learning outcomes, evaluation, and problems faced. This study described the English Language Education students’ view of the independent assessment, learning outcome, and evaluation of English online learning from the perspective of English Language Education students. The researchers employed a descriptive quantitative approach and a survey method to collect the data. This study included 100 participants using a purposive sampling technique. For data collection, the researchers employed a questionnaire with 33 questions sent via Google Forms and disseminated to WhatsApp groups and an interview. The data were then coded and tabulated using percentage-based basis values. The findings of this study indicated that, first, students' attitudes regarding the independent assessment of e-learning assessment were 85% showing a favorable result. In the meantime, certain lecturers' respondents needed to provide more feedback and were absent from certain lecturers during learning. Second, the student's view of the learning outcome of using e-learning was positive (68%) because the online meeting coincided with the learning process. Third, the students' perspectives on the evaluation of using e-learning fall under the category of the fair. (65%) During the pandemic, poverty has hindered students' access to and involvement in learning. Those who come from economically disadvantaged families cannot provide appropriate resources for online learning. Long-term lack of infrastructure and access will jeopardize educational achievements.